The fungivorous amoeba Protostelium aurantium targets redox homeostasis and cell wall integrity during intracellular killing of Candida parapsilosis. (13th September 2021) - Radosa, Silvia; Sprague, Jakob L.; Lau, Siu‐Hin; Tóth, Renáta; Linde, Jörg; Krüger, Thomas; Sprenger, Marcel; Kasper, Lydia; Westermann, Martin; Kniemeyer, Olaf; Hube, Bernhard; Brakhage, Axel A.; et al.
Abstract: Predatory interactions among microbes are major evolutionary driving forces for biodiversity. The fungivorous amoeba Protostelium aurantium has a wide fungal food spectrum including foremost pathogenic members of the genus Candida . Here we show that upon phagocytic ingestion by the amoeba, Candida parapsilosis is confronted with an oxidative burst and undergoes lysis within minutes of processing in acidified phagolysosomes. On the fungal side, a functional genomic approach identified copper and redox homeostasis as primary targets of amoeba predation, with the highly expressed copper exporter gene CRP1 and the peroxiredoxin gene PRX1 contributing to survival when encountered with P. aurantium . The fungicidal activity was largely retained in intracellular vesicles of the amoebae. Following their isolation, the content of these vesicles induced immediate killing and lysis of C. parapsilosis in vitro. Proteomic analysis identified 56 vesicular proteins from P. aurantium . Although completely unknown proteins were dominant, many of them could be categorised as hydrolytic enzymes targeting the fungal cell wall, indicating that fungal cell wall structures are under selection pressure by predatory phagocytes in natural environments. Take Away: The amoeba Protostelium aurantium feeds on fungi, such as Candida parapsilosis . Ingested yeast cells are exposed to reactive oxygen species. A copper exporter and a peroxiredoxin contribute to fungal defence. Yeast cells undergo intracellular lysis. Lysis occurs via a cocktail of hydrolytic enzymes from intracellular vesicles. Abstract : The amoeba Protostelium aurantium feeds on fungi, including human pathogenic species such as Candida parapsilosis . Following ingestion, yeast cells are exposed to reactive oxygen species (ROS) in an acidified phagosome (H+). A copper exporter (CRP1) and a peroxiredoxin (PRX1) contribute to defence while lysis occurs via hydrolytic enzymes from intracellular vesicles of the amoeba.